Impact of agitation in long‐term care residents with dementia in the United States. (27th August 2021) - Fillit, Howard; Aigbogun, Myrlene S.; Gagnon‐Sanschagrin, Patrick; Cloutier, Martin; Davidson, Mikhaïl; Serra, Elizabeth; Guérin, Annie; Baker, Ross A.; Houle, Christy R.; Grossberg, George
Abstract: Objectives: To describe characteristics and compare clinical outcomes including falls, fractures, infections, and neuropsychiatric symptoms (NPS) among long‐term care residents with dementia with and without agitation. Methods: A cross‐sectional secondary analysis of administrative healthcare data was conducted whereby residents with dementia residing in a long‐term care facility for ≥12 months were identified from the AnalytiCare LLC database (10/2010–06/2014) and were classified into mutually exclusive cohorts (Agitation Cohort or No‐Agitation Cohort) based on available agitation‐related symptoms. Entropy balancing was used to balance demographic and clinical characteristics between the two cohorts. The impact of agitation on clinical outcomes was compared between balanced cohorts using weighted logistic regression models. Results: The study included 6, 265 long‐term care residents with dementia among whom, 3, 313 were included in the Agitation Cohort and 2, 952 in the No‐Agitation Cohort. Prior to balancing, residents in the Agitation Cohort had greater dementia‐related cognitive impairment and clinical manifestations compared to the No‐Agitation Cohort. After balancing, residents with and without agitation, respectively, received a median of five and four distinct types of medications (including antipsychotics). Further, compared to residents without agitation, those with agitation were significantly more likely to have a recorded fall (OR = 1.58), fracture (OR = 1.29), infection (OR = 1.18), and other NPS (OR = 2.11). Conclusions: Agitation in long‐term care residents with dementia was associated with numerically higher medication use and an increased likelihood of experiencing falls, fractures, infections, and additional NPS compared to residents without agitation, highlighting the unmet need for effective management of agitation symptoms in this population. Key points: Agitation symptoms in long‐term care residents with dementia can be disabling and lead to a loss of independent function This study suggests that agitation is associated with higher use of polypharmacy, including antipsychotics, and an increased likelihood of falls, fractures, infections as well as other neuropsychiatric symptoms Together, these outcomes present a major burden not only to the patient, but also to the long‐term care facilities, caregivers, and healthcare system Findings of this study highlight the complexity of care for long‐term care residents with dementia and the current unmet need for effective management of agitation symptoms in this setting